New Fire Extinguishing Powder Compositions Based on Powder Waste of Production Enterprises - Rakhmat, Boltaboev; Rustamovich, Talibdjanov Isroil; Abdukadirovich, Tulaganov Odil (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents research data on the fire extinguishing ability of powder combustion inhibitors obtained on the basis of waste from the production of mineral fertilizers. The factors influencing the extinguishing process with powder compositions are investigated, such as dilution of the combustible medium with gaseous decomposition products of the powder or the powder cloud itself, cooling of the combustion zone as a result of heat expenditure on heating the powder particles, the effect of fire blocking achieved when the flame passes through narrow channels and inhibition of the combustion process with gaseous products of evaporation of decomposition. It was determined that when tested in the process of extinguishing the resulting dispersed composition of a fire extinguishing agent based on phosphogypsum in a mixture with sols, its friability increases, which in turn facilitates its use in the extinguishing process. It has been established that with a sol content of 30%, the heat of combustion is effectively carried away from the combustion zone and, as a result, leads to a decrease in the fire extinguishing time.